Cobalt fill for advanced interconnects - Bekiaris, Nikolaos; Zhiyuan Wu; Ren, He; Naik, Mehul; Jin Hee Park; Lee, Mark; Tae Hong Ha; Wenting Hou; Bakke, Jonathan R.; Gage, Max; You Wang; Jianshe Tang (Proceedings of the IEEE International Interconnect Technology Conference, 2017)
Cobalt as a material promises to change the conductor landscape in many areas, particularly logic contact and interconnect. In this paper, we focus on Cobalt as the conductor for logic interconnect - a potential Cu replacement. We demonstrate Co fill capability down to 10nm CD, and show that Co-Cu resistivity cross-over will occur below 14nm CD. Single damascene Co-ULK structures are used to establish an optimized metallization stack with robust CMP performance that has electromigration and TDDB reliability better than copper interconnect.